Force experienced by the head during heading is influenced more by speed than the mechanical properties of the football - Tierney, G. J.; Power, J.; Simms, C. (Scandinavian Journal of Medicine & Science in Sports, 2021)
There are growing concerns about the risk of neurodegenerative diseases associated with heading in football. It is essential to understand the biomechanics of football heading to guide player protection strategies to reduce the severity of the impact. The aim of this study was to assess the effect of football speed, mass, and stiffness on the forces experienced during football heading using mathematical and human body computational model simulations. Previous research indicates that a football header can be modeled as a lumped mass mathematical model with elastic contact. Football headers were then reconstructed using a human body modeling approach. Simulations were run by independently varying the football mass, speed, and stiffness. Peak contact force experienced by the head was extracted from each simulation. The mathematical and human body computational model simulations indicate that the force experienced by the head was directly proportional to the speed of the ball and directly proportional to the square root of the ball stiffness and mass. Over the practical range of ball speed, mass, and stiffness, the force experienced by the head during football heading is mainly influenced by the speed of the ball rather than its mass or stiffness. The findings suggest that it would be more beneficial to develop player protection strategies that aim to reduce the speed at which the ball is traveling when headed by a player. Law changes reducing high ball speeds could be trialed at certain age grades or as a phased introduction to football heading.